2021
DOI: 10.7554/elife.68758
|View full text |Cite
|
Sign up to set email alerts
|

Infrared molecular fingerprinting of blood-based liquid biopsies for the detection of cancer

Abstract: Recent omics analyses of human biofluids provide opportunities to probe selected species of biomolecules for disease diagnostics. Fourier-transform infrared (FTIR) spectroscopy investigates the full repertoire of molecular species within a sample at once. Here, we present a multi-institutional study in which we analysed infrared fingerprints of plasma and serum samples from 1639 individuals with different solid tumours and carefully matched symptomatic and non-symptomatic reference individuals. Focusing on bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…Several N-glycan signatures, such as sialylation, fucosylation, bisecting GlcNAcylation, and branching, are regulated by various glycosyltransferase activities, and their synthetic pathways could influence each other. Although discriminating three or more diseases by discriminant analysis using N-glycan signatures has been limited, an ML approach combined with omics data has been used for early detection of diseases, including cancer [16][17][18][19] and seems to be suitable for extraction of disease-specific N-glycan features and precise discrimination between benign and malignant conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several N-glycan signatures, such as sialylation, fucosylation, bisecting GlcNAcylation, and branching, are regulated by various glycosyltransferase activities, and their synthetic pathways could influence each other. Although discriminating three or more diseases by discriminant analysis using N-glycan signatures has been limited, an ML approach combined with omics data has been used for early detection of diseases, including cancer [16][17][18][19] and seems to be suitable for extraction of disease-specific N-glycan features and precise discrimination between benign and malignant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses to extract disease‐specific N ‐glycan signatures from vast amounts of N ‐glycomics data on complex N ‐glycan structures and their synthetic pathways are limited. Therefore, ML approaches could be an important tool for these analyses 16–19 . We aimed to simultaneously detect nine urological diseases including five cancers (RCC, BCa, UTUC, PC, and GCT) and three benign diseases (BPH, US, and UTI) using a diagnostic modeling ML approach with Ig N ‐glycan signature data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average of the correctness of the ten results is used as an estimate of the accuracy of the algorithm. This approach aims to identify the signals of cancer from a known patient cohort to develop a trained classification model and then use this information to predict the presence of cancer in an unknown population [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, during cisplatin-induced drug resistance, the expression of mir-146a-5p in NSCLC cell lines or exosomes decreased gradually, while overexpression of mir-146a-5p was shown to reverse DDP resistance in A549 cells. These findings suggested that inhibition of exosome formation and release may be a potential new strategy for the treatment of lung cancer [ 50 ].…”
Section: Introductionmentioning
confidence: 99%